2016
DOI: 10.1371/journal.pone.0166134
|View full text |Cite
|
Sign up to set email alerts
|

The Biogeographic South-North Divide of Polygonatum (Asparagaceae Tribe Polygonateae) within Eastern Asia and Its Recent Dispersals in the Northern Hemisphere

Abstract: Eastern Asia (EA) is a key region for the diversification of flowering plants in the Northern Hemisphere, but few studies have focused on the biogeographic history within EA in the context of the other northern continents. Polygonatum is an important medicinal genus widely distributed in the Northern Hemisphere with its highest species richness in EA, and it represents an excellent model for studying the evolution of biogeographic patterns in this region. Divergence time estimation was used to examine the biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…It has often been suggested that the east-west-orientated aridity belt acted as a climate barrier between nEA and sEA (Donoghue et al, 2001;Guo et al, 2008;Bai et al, 2016). A similar pattern was also reported for Polygonatum, Pistacia, and Quercus, that the arid zone acted as a barrier of their gene flow between southern and northern parts of EA (Xie et al, 2014;Wang et al, 2016;Deng et al, 2018). Our biogeographic results also revealed multiple recent migrations/exchanges between nEA and sEA in the late Miocene to present (Fig.…”
Section: Divergence Times and Biogeographysupporting
confidence: 87%
See 3 more Smart Citations
“…It has often been suggested that the east-west-orientated aridity belt acted as a climate barrier between nEA and sEA (Donoghue et al, 2001;Guo et al, 2008;Bai et al, 2016). A similar pattern was also reported for Polygonatum, Pistacia, and Quercus, that the arid zone acted as a barrier of their gene flow between southern and northern parts of EA (Xie et al, 2014;Wang et al, 2016;Deng et al, 2018). Our biogeographic results also revealed multiple recent migrations/exchanges between nEA and sEA in the late Miocene to present (Fig.…”
Section: Divergence Times and Biogeographysupporting
confidence: 87%
“…The Asian/North American disjunctions can be explained by the Bering land bridge, which was available until 3.5-5.0 Ma (Elias et al, 1996); this dispersal route played a significant role for the initial range expansion of Saxifraga to Asia and for further dispersal throughout the Northern Hemisphere (Ebersbach et al, 2017a). The Bering land bridge dispersal route has been proposed for a number of other plant groups (Nie et al, 2006(Nie et al, , 2007Zhu et al, 2013;Wei et al, 2015;Wang et al, 2016;Wen et al, 2016;Graham, 2018). Although the North Atlantic land bridges were also available in the Oligocene, they seem less likely because there are no records of extant species or fossils of sect.…”
Section: Divergence Times and Biogeographymentioning
confidence: 99%
See 2 more Smart Citations
“…Tamura et Ogisu from Polygonatum (Tamura et al 1997a) and found the topological difference of Heteropolygonatum and its relative taxa: (1) (Heteropolygonatum + Disporopsis) + Polygonatum and (2) (Heteropolygonatum + Polygonatum) + Disporopsis (Tamura et al 1997b). Later, the former case was supported by Meng et al (2014) and Wang et al (2016), whereas the latter one was supported by Floden and Schilling (2018) and Zhao et al (2019). The genus Polygonatum was divided into three sections, based on four chloroplast molecular markers, leaf arrangement and basic chromosome number: (1) Polygonatum sect.…”
Section: Introductionmentioning
confidence: 96%